Evaluation of Somaclones Peanut Plants Regenerated from Repeat Cycles of In Vitro Selection Against Drought Stress - A Farid Hemon; , Sudarsono (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2010)
The objective of this research was to evaluate the response of somaclonal peanut plants regenerated from repeated cycles of in vitro selection on medium containing 15% polyethylene glycol (PEG; w /v, corresponding to - 0.41 Mpa osmotic potential) against drought stress. The R2 generation of peanut plants were used in this experiment with cv